Procesos productivos y amenazas de aborto en las trabajadoras de la florícola Blooming Acres. Propuesta de un sistema de intervención. - Icaza Mejía, Néstor Germánico (2015)
This study of research addresses both theoretical and practical productive processes focus on the health and safety at work. It was worked on the analysis of the productive processes and threats of abortion in the flowers production enterprise BLOOMING ACRES S. A. at the Cotopaxi province for designing an intervention system. It begins with a description of work areas and number of people who make up, then performed an evaluation of the production processes by applying ergonomic methods that allow us to obtain information of the following variables raising of charges, forced positions, mechanical risks, repetitive movements, which allowed to identify unfavorable aspects that have interference in the threats of abortion of female workers. Pregnancy is an inherent aspect of sexual reproductive life and health and safety of workers, they can be properly monitored with regular application of prevention and protection processes at work. In the field study it was proved that factors exist, they have interference in the reproductive health, therefore there must take corrections that minimize or eliminate expound factors for having a sure job. It permit affirm that the hypothesis had been verifying sustainable to prove in the research. For which quantitative methods of analysis that showed changes in production processes that are harmful to the pregnant worker there proposing a guide to safe motherhood was applied.